Error-Based Pedagogy in Teaching Factory: A Case Study on Leveraging Production Failures to Foster Students’ Creativity and Learning Autonomy - Sarjoko, Sarjoko; Suharno, Suharno; Widiastuti, Indah; Cahyono, Budi Tri (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
This study examines the implementation of error-based pedagogy in a TEFA environment and its role in transforming production failures into meaningful learning experiences. Employing a qualitative case study design, the research was conducted in a machining specialization program at a vocational high school in Indonesia. Data were collected through participatory observation and in-depth interviews involving teachers and students, focusing on their interactions during episodes of production failure. The data were analyzed using an interactive model with iterative coding procedures, leading to the identification of key patterns related to students’ creativity and learning autonomy. The findings reveal a pedagogical shift from a production-oriented approach toward a reflective learning ecosystem, where errors are reframed as cognitive triggers rather than operational setbacks. Students demonstrated increased creativity through adaptive problem-solving, including the development of improvised tools and the modification of machining strategies. In parallel, learning autonomy emerged through independent troubleshooting, risk-informed decision-making, and self-regulated quality control. These processes were supported by a facilitative teaching approach that encouraged metacognitive reflection without immediate intervention. This study contributes to vocational education by providing empirical evidence that error-based pedagogy can serve as an effective strategy for fostering creativity and learning autonomy in authentic production settings. It also offers practical insights into how production failure can be leveraged as a productive learning resource without compromising operational objectives.